Body Image Perception and Eating Behavior as Determinants of Nutritional Status Among Adolescent Girls - Syafiq Maulana; Mohammad Dimas Dwihartono Syariat; Fatahillah Tsabit Fatoni; Nurlaili Susanti (FORIKES, 2026)
Body image perception and eating-related behaviors play an important role in determining adolescents’ nutritional status. This study aimed to examine the association between body image perception, eating behavior, dietary patterns, and nutritional status among adolescent girls using a cross-sectional research design. A total of 80 adolescent girls were recruited in August 2024. Data were collected using the Multidimensional Body-Self Relations Questionnaire–Appearance Scale (MBSRQ-AS) to assess body image perception, a Food Frequency Questionnaire (FFQ) to evaluate dietary patterns, and the Eating Behavior Pattern Questionnaire (EBPQ) to measure eating behavior. Nutritional status was determined using Body Mass Index (BMI). Data were analyzed using chi-square tests with contingency coefficient analysis. The results showed that negative body image perception was significantly associated with underweight nutritional status (p=0.006; C=0.335). Adolescents with healthy eating behavior were more likely to have normal nutritional status compared to those with poor eating behavior (p=0.012; C=0.316). Dietary patterns were not significantly associated with nutritional status (p=0.108; C=0.229). In conclusion, body image perception and eating behavior were significantly associated with nutritional status among adolescent girls, whereas dietary patterns showed no significant association.Keywords: body image perception; eating behavior; dietary patterns; nutritional status; adolescent girls